„Autokratische Redistribution - Institutionen, Legitimation und die Umverteilung von Einkommen in Nicht-Demokratien“ - Lott, Lars; Croissant, Aurel (Zeitschrift für vergleichende Politikwissenschaft, 2018)
The purpose of this article is to test if institutional approaches and legitimation-oriented explanations in comparative authoritarianism research can account for the differences in redistribution of income in autocracies. In order to address this question, the study analyses data on income redistribution for 122 autocracies worldwide between 1960 and 2010. The existing literature suggests that authoritarian institutions and strategies of regime legitimation affect policy outputs in autocracies. This article develops an informal model that explains income redistribution as the outcome of bargaining between the dictator, political elites and the masses over the level of income taxation and social welfare expenditures. The findings of our statistical analysis suggest that there are substantial differences between income redistribution between different types of authoritarian regimes and their strategies of regime legitimation: Communist regimes exhibit the highest average income redistribution while monarchies have the lowest redistribution rate. However, legitimation strategies of different types of autocracy cannot account for the differences in social welfare expenditures in authoritarian regimes. In contrast, authoritarian political institutions explain different levels of social welfare expenditure in autocracies, but cannot account for the differences in income redistribution. Overall, institutional and legitimation-centred approaches contribute to a better understanding of differences in income redistribution between autocracies, but their explanatory power is limited. Therefore, the article concludes with some considerations concerning avenues for future research.
Gesehen am 06.02.2019
Keywords: Erde